ANALISIS PERBANDINGAN ROI DAN EVA DALAM MENILAI KINERJA KEUANGAN SEKTOR PHARMACEUTICALS & HEALTH CARE RESEARCH - Syavia Alvi Maulidya Arma; Deni Ramdani (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to analyze the comparison of Economic Value Added (EVA) and Return On Investment (ROI) in assessing the performance of the Pharmaceuticals & Health Care Research financial subsector listed on the Indonesia Stock Exchange (IDX). The research was conducted using a descriptive method with a quantitative approach, where the data obtained will be processed and analyzed to draw conclusions. The research was conducted on the analysis of numerical data obtained through financial reports published on the Indonesia Stock Exchange (IDX). The observation period was from 2020-2021. The results showed that the financial performance of the Pharmaceuticals & Health Care Research sub-sector using EVA and ROI analysis showed that PT Kalbe Farma Tbk. (KLBF) is a company with the best economic value creation. Meanwhile, if measured using the analysis of Return On Investment (ROI), the results showed that PT Industri Jamu and Pharmacy Sido Muncul Tbk. (SIDO) as the company with the best investment turnover rate. The results of the overall analysis show that EVA is more appropriate to be used to assess company performance than ROI.